Komunikasi Lingkungan Pemerintah Membangun Kesadaran Masyarakat Tentang Kegiatan Penambangan Emas Ilegal Di Kabupaten Kuantan Singingi - Pratama, Frendika; Muhammad Firdaus (Journal of Research and Development on Public Policy, 2023)
The decline in the water quality of the Batang Kuantan river is caused by excessive human activity, and what has attracted the most attention is the activity of Unlicensed Gold Miners (PETI), PETI activities are people who changed jobs from being farmers to becoming gold miners, due to economic factors. PETI makes river water black and smelly, this is caused by the washing and panning process using mercury or quicksilver. To make the public aware, environmental communication is needed which explains the state of the environment, its impacts and handling, and the main communicator in this environmental communication is the Government (DLH) which is committed to environmental management. Therefore, this research aims to find out the government's environmental communication planning (DLH) as a communicator in environmental conservation programs, to find out the implementation of the Government (DLH) in implementing environmental damage prevention programs. This research uses a qualitative method with a descriptive approach with the technique of determining research subjects, namely purposive . The author uses data collection techniques through interviews, observation and documentation. The number of informants was five people according to the criteria determined purposively. The data analysis technique in this research uses the Miles and Huberman Model and the data validity checking technique, namely triangulation. The results of the research show that environmental communication carried out by the Government (DLH) in implementing the environmental damage prevention program carried out by the Government (DLH) requires communication planning. The planning carried out consists of analyzing the problem, analyzing the audience, formulating goals, developing messages, planning media production. Apart from that, the implementation of environmental communication activities from DLH includes socialization actions, raids/raids, and appeals to the community in Cerenti District, especially the community of Sikakak Village.